THE USE OF ENGLISH CARTOON PROGRAMS IN ACQUIRING FOREIGN LANGUAGE ON 3.5 YEARS OLD CHILD; KRASHEN’S THEORY - Sianipar, Yules (Proceedings of the International Conference on Education, 2023)
This study aims to find out how English-language cartoon films can help in acquiring foreign languages at an early age, focused on English. This research is qualitative descriptive research where the research uses the case study method (case and field method). The research’s problem is finding out how far the use of English-language cartoons can help children understand English. From the monitoring process, data were collected in a form of videos when the child watched cartoons and when interacting with other people using English and videos of the child practicing English in the form of singing or speech. The results of the study show that even a three-year-old child can speak and communicate in good English and understand it, although there is still a mixed-language process carried out by the subject. Early absorption can help children to become skilled foreign language users and understand them well regardless of the mistakes made because the child develops to understand the foreign language, not through the teaching process. Still, the understanding gained and learned from the cartoons watched.